2012
DOI: 10.5423/ppj.2012.28.2.207
|View full text |Cite
|
Sign up to set email alerts
|

Mode of Action of Streptomycin Resistance in the Citrus Canker Pathogen (Xanthomonas smithii subsp. citri) in Jeju Island

Abstract: It has been known that streptomycin resistance in bacteria can occur as a results of chromosomal mutation or through gene acquisition or both. Chromosomal mutations for resistances are point mutations in the rpsL gene, which alter ribosomal protein S12. Acquired resistance has occurred when an Sm R plasmid carrying transposon Tn5393 with tandem strA-strB gene is transferred by conjugation. A total of 686 isolates of Xanthomonas smithii subsp. citri causal agent of citrus canker disease were collected from 26 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 13 publications
1
25
0
Order By: Relevance
“…Copper-based bactericides and streptomycin antibiotics have been used in the attempt to control this disease (Behlau et al, 2011; Graham et al, 2008). Nevertheless, they are relatively ineffective on certain Xcc strains (Voloudakis et al, 2005) which have developed resistance to these disease control products (Hyun et al, 2012). Therefore, our aim was to find efficacious alternative citrus canker control measures.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Copper-based bactericides and streptomycin antibiotics have been used in the attempt to control this disease (Behlau et al, 2011; Graham et al, 2008). Nevertheless, they are relatively ineffective on certain Xcc strains (Voloudakis et al, 2005) which have developed resistance to these disease control products (Hyun et al, 2012). Therefore, our aim was to find efficacious alternative citrus canker control measures.…”
Section: Discussionmentioning
confidence: 99%
“…3). Therefore, it is a promising candidate as a biocontrol agent against the streptomycin-resistant strains Xcc M4-9 (Hyun et al, 2012). The ethyl acetate extract may have contained potent secondary metabolites which suppressed the growth of Xcc .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has also been shown that copper resistance genes are naturally present within the citrus-associated bacterial microflora in areas exposed to high copper treatment pressure and have the ability to be integrated into the genome of X. citri pv. citri strains were found both in streptomycin-treated citrus orchards and in untreated orchards in Jeju island (South Korea) where streptomycin is registered to control citrus canker (Hyun et al, 2012). Major pathogenicity genes are also plasmid borne and could be exchanged among strains by horizontal gene transfer (El Yacoubi et al, 2007).…”
Section: Other Characteristics Of the Pest Affecting The Probability mentioning
confidence: 99%